Analisis Rasion Laporan Keuangan Sebagai Alat untuk Menilai Tingkat Keberhasilan Kinerja Keuangan di PT Argha Karya Prima Industry Tbk di Bursa Efek Indonesia - Ilham Sonata; Julienda Br Harahap; Selianus Gulo (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2022)
The Indonesia Stock Exchange (IDX) or the Indonesia Stock Exchange (IDX) is a party that organizes and provides a means to bring together securities buying and selling offers of other parties with the aim of trading securities between them (Indonesia Free, 2020). This type of research is quantitative by using the sampling technique is purposive sampling. To collect data samples, researchers used secondary data, namely documentation on the Indonesia Stock Exchange (IDX). Then a time series analysis is carried out, namely a comparative analysis of financial ratios from one period to another where ratio analysis is used, namely financial ratio analysis consisting of ratios, solvency ratios, profitability ratios, and activity ratios. This study aims to analyze the ratio of financial statements as a tool to assess the level of success of financial performance at Pt. Argha Karya Prima Industry Tbk on the Indonesia Stock Exchange. To find out to what extent the development of performance at PT. Argha Karya Prima Industry Tbk on the Indonesia Stock Exchange. From a financial point of view. With the results of research from the liquidity ratio seen from the current ratio and fixed ratio, the company is in good condition,